First Principles Study of the Electronic, Optical, Elastic, and Thermal Properties of Double Perovskite Sr₂MgWO₆ for Optoelectronic Applications - Pokharel, Peshal; Yadav, Shashit Kumar; Adhikari, Devendra; Pantha, Nurapati (Journal of Institute of Science and Technology, 2025)
The double perovskite Sr₂MgWO₆ exhibits outstanding mechanical, electronic, and optical properties, making it a potential candidate for high-performance optical and optoelectronic applications. In this regard, we investigated the electronic, magnetic, optical, elastic, and structural properties of the double perovskite Sr₂MgWO₆ using the Quantum ESPRESSO code. Structural stability has been confirmed through calculations of formation energy and the tolerance factor. The material exhibited a wide-band-gap (3.18 eV) semiconductor with intense polarization (ε₁(ω) = 12.46) and a decreasing ε₂(ω) peak with photon energy. Elastic parameters, including elastic constants, bulk modulus, shear modulus, and Young's modulus, were determined using the stress-strain method. The calculated elastic constants satisfied Born-Huang criteria for mechanical stability. Calculated high value of bulk modulus (B), and Young's modulus (E) indicated the material's high resistance to volumetric deformation and stiffness, with a moderate shear modulus. A G/B ratio greater than 0.57, a negative Cauchy constant, and a low Poisson's ratio collectively indicated brittle behavior. The calculated Debye temperature of 492.34 K and specific heat capacity (Cᵥ) of 373.4 J/mol-K further emphasized the mechanical strength, thermal stability, and high thermal conductivity of the material. These findings suggest that Sr₂MgWO₆ could be an excellent material for optical waveguides, light-emitting devices, and other optoelectronic technologies.